Effect Of Core Stability Exercises and Balance Training in Postural Control Among Children with Down Syndrome : Stability Exercises and Balance Training in Postural Control Among Children - Zulfiqar, Hunza; Hafiz Muneeb Ur Rehman; Razzaq, Ayesha; Zaib Un Nisa; Maryam Hina; Bashir, Humaira; Saeed, Hijab; Ashraf, Najam us Sahar (Pakistan BioMedical Journal, 2022)
Posture, balance, and movement issues are common in children with Down syndrome. Emerging research suggests that balance training may be advantageous for children with Down syndrome, making it a crucial component of physical activity programmes. Objective: to ascertain the impact of balance training and activities for core stability on postural control in kids with Down syndrome. Methods: single blinded RCT study was conducted, in which assessor was kept blind. While taking into account inclusion and exclusion criteria, children with Down syndrome were randomly divided into two groups with ages ranging from 5 to 17 years. There were 20 patients in the sample. Exercises for core stability were given to Group 2 and balance training to Group 1. The time between treatments was six weeks. The Comprehensive Rehabilitation facility Chakwal is where the data is gathered. The pre- and post-values of postural stability were measured using the paediatric Berg balance scale. Results: The present results are significantly better in the group B than in the group A. Core stability exercises shows better results than balance training. Conclusion: According to the results of the current study from the data of before the treatment and after the treatment, it revealed a positive change. In the duration of six weeks the core stability exercises were more effective than balance training in developing postural control among children with Down syndrome.